The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/conphys/coy045
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime glucocorticoid profiles in baleen of right whale calves: potential relationships to chronic stress of repeated wounding by Kelp Gulls

Abstract: Baleen from stranded carcasses of five right whale calves (four southern and one North Atlantic) contain cortisol and corticosterone patterns that may represent longitudinal profiles of stress exposure over time. Calves with high wounding from Kelp Gulls had markedly higher glucocorticoids in postnatal baleen than did less wounded and unwounded calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
(80 reference statements)
2
17
0
Order By: Relevance
“…documented pregnancies (NARW, baleen; Hunt et al , 2017a ). Similarly, both GCs show elevations during confirmed severe stressors such as chronic entanglement in fishing gear (NARW, Lysiak et al , 2018 ), repeated wounding (southern right whale, Eubalaena australis ; Fernández Ajó et al , 2018 ), and prolonged chronic illness (humpback whale; Hunt, unpublished data). In this study, there was only one known case of prolonged chronic stress independently confirmed through sightings data, the NARW that experienced possible disease and a definite entanglement in 1997–98.…”
Section: Discussionmentioning
confidence: 94%
“…documented pregnancies (NARW, baleen; Hunt et al , 2017a ). Similarly, both GCs show elevations during confirmed severe stressors such as chronic entanglement in fishing gear (NARW, Lysiak et al , 2018 ), repeated wounding (southern right whale, Eubalaena australis ; Fernández Ajó et al , 2018 ), and prolonged chronic illness (humpback whale; Hunt, unpublished data). In this study, there was only one known case of prolonged chronic stress independently confirmed through sightings data, the NARW that experienced possible disease and a definite entanglement in 1997–98.…”
Section: Discussionmentioning
confidence: 94%
“…Popular choices are hair [e.g. 10 , [11] , [12] , [13] ] and feathers [14 , 15] , while other examples include whale baleen [16 , 17] , claws [18] , snakeskin [19] and reptilian scutes [20] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…Fernández Ajó et al . () attributed postnatal increases in baleen GCs to chronic stress from repeated wounding by kelp gulls ( Larus dominicanus ) in two southern right whale calves ( E. australis ). Variation in baleen GCs associated with energetically demanding life history stages such as pregnancy and lactation has been reported in E. glacialis (Hunt et al .…”
Section: The Mean (± Sd) Baseline (± Sd) and Maximum Values For Cormentioning
confidence: 99%
“…Lysiak et al (2018) found elevated corticosterone in a baleen plate from a North Atlantic right whale (E. glacialis) with a chronic fishing gear entanglement that was eventually fatal. Fernández Ajó et al (2018) attributed postnatal increases in baleen GCs to chronic stress from repeated wounding by kelp gulls (Larus dominicanus) in two southern right whale calves (E. australis). Variation in baleen GCs associated with energetically demanding life history stages such as pregnancy and lactation has been reported in E. glacialis (Hunt et al 2017a).…”
mentioning
confidence: 99%